Handbook of multi-commodity markets and products : structuring, trading and risk management - Roncoroni, Andrea; Fusai, Gianluca; Cummins, Mark, 1968- (Chichester, West Sussex : John Wiley & Sons Ltd, 2015)
The comprehensive guide to working more effectively within the multi-commodity market. The Handbook of Multi-Commodity Markets and Products is the definitive desktop reference for traders, structurers, and risk managers who wish to broaden their knowledge base. This non-technical yet sophisticated manual covers everything the professional needs to become acquainted with the structure, function, rules, and practices across a wide spectrum of commodity markets. Contributions from a global team of renowned industry experts provide real-world examples for each market, along with tools for analyz.
3.1.3 Liquefied Natural Gas3.1.4 Shale Gas; 3.2 Natural Gas Contracting and Pricing; 3.2.1 Natural Gas Price Formation; 3.3 Financial Natural Gas Markets; 3.3.1 Exchange-Based Markets; 3.3.2 Natural Gas Futures; 3.3.3 Natural Gas Options; 3.3.4 OTC Markets and Products; References; 4 Electricity Markets and Products; 4.1 Market Structure and Price Components; 4.1.1 Spot and Forward Markets; 4.1.2 Supply and Demand Interaction; 4.1.3 Electricity Derivatives; 4.1.4 Power Price Models; 4.1.5 Spot Price Analysis (IPEX Case); 4.1.6 Forward Price Analysis (EEX Case).
Includes bibliographical references and index.
Print version record.
Keywords: Commodity exchanges; Commodity exchanges; Derivative securities -- Databases; BUSINESS & ECONOMICS -- Finance; Commodity exchanges; Electronic books; Electronic books